Designing a multicomponent intervention to support caregivers of persons with dementia in primary care in Spain: a qualitative study of family and professional carers - Constanza Jacques-Aviñó; Carina Aguilar Martín; Alessandra Queiroga Gonçalves; Claudia Curto Romeu; Gerard Mora López; Ester Gavaldà Espelta; Núria Brunet Reverté; Maria del Mar Lleixà Fortuño; Maria Ferre Ferrate; Macarena Pozo Ariza; Carme Ferre Grau (BMJ Open)
Objective The purpose of this study was to explore experiences of family and professional caregivers of persons with dementia in order to design a tailored community-based support programme.Design A two-stage study was deployed. First, qualitative research draws on three focus groups. Two of these comprised family caregivers and the third was made up of care provision professionals. Thematic content analysis was conducted by interpretative description for applied practice. Second, an experience-based codesign methodology was applied to design a tailored support programme in accordance with carers’ demands and contextual realities.Setting and study period Rural region in Catalonia, at northeast of Spain. March–June 2019.Participants We interviewed 12 family caregivers and 8 primary care providers.Results 10 main themes were identified: caregivers’ feelings, repercussions of caregiving in caregivers’ lives, education about dementia and caring skills, education about time management and self-care, caregivers’ needs to receive more information and training, improved patients’ follow-up and social assistance and more psychologic support. Finally, three themes related to caregivers’ demands: social services resources, multidisciplinary approach programmes and support from other caregivers. From these results, a multicomponent, professionally led community-based intervention was designed. The main components were the following: education and caring skills, professional psychological support, and social and community resources.Conclusion This study allowed the design of a multicomponent support intervention for family caregivers of persons with dementia aimed at reducing their burden and improving their quality of life in ways consistent with their actual needs and the available local resources.